2014
DOI: 10.1186/1472-6947-14-2
|View full text |Cite
|
Sign up to set email alerts
|

The Québec BCG Vaccination Registry (1956–1992): assessing data quality and linkage with administrative health databases

Abstract: BackgroundVaccination registries have undoubtedly proven useful for estimating vaccination coverage as well as examining vaccine safety and effectiveness. However, their use for population health research is often limited. The Bacillus Calmette-Guérin (BCG) Vaccination Registry for the Canadian province of Québec comprises some 4 million vaccination records (1926-1992). This registry represents a unique opportunity to study potential associations between BCG vaccination and various health outcomes. So far, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…[34][35][36] Some authors who assessed preferences retrospectively found that most people preferred a passive role in decision-making, and when preferences were asked in general like in our study, the majority of patients more often preferred a passive role than when were asked about a more specific treatment option. 19 In general, our results are consistent with those of Cuevas, 4,15 who argued that SDM occurs very occasionally in Spanish National Health System despite of previous positive attitudes observed in our medical outpatient setting.…”
Section: Figure 1 Participant Inclusion Flow Chartsupporting
confidence: 92%
See 3 more Smart Citations
“…[34][35][36] Some authors who assessed preferences retrospectively found that most people preferred a passive role in decision-making, and when preferences were asked in general like in our study, the majority of patients more often preferred a passive role than when were asked about a more specific treatment option. 19 In general, our results are consistent with those of Cuevas, 4,15 who argued that SDM occurs very occasionally in Spanish National Health System despite of previous positive attitudes observed in our medical outpatient setting.…”
Section: Figure 1 Participant Inclusion Flow Chartsupporting
confidence: 92%
“…Our study adds to the existing research that showed that younger patients more often prefer to take a more active role in medical decisions. 19 Education level was also associated in our study with the preferences in the degree of participation in the decision-making process.…”
Section: Figure 1 Participant Inclusion Flow Chartmentioning
confidence: 60%
See 2 more Smart Citations
“…The advancing goals of health information exchange on a wider scale will streamline this process [14]. This includes deterministic rather than probabilistic patient record matching [15,16], patient governance over their own health information [17], and simpler interoperability with other databases.…”
Section: Discussionmentioning
confidence: 99%